Use of galactomannan edible coating application and storage temperature for prolonging shelf-life of “regional” cheese - Cerqueira, M. A. (2010)
The objectives of this work were to determine the influence of the application of two different coatings (galactomannan and chitosan) and of storage temperature on the gas exchange rate of “Regional” cheese; subsequently, the coating that showed the greatest influence on the cheese gas exchange and simultaneously decreased the O2 consumption (RO2) and the CO2 production (RCO2) rates was applied on cheese, being the shelf-life parameters monitorized through the performance of chemical and microbiological analyses. Both coatings caused a reduction of RO2 and RCO2 of the cheese (between 0.19- and 1.30-fold for RO2 and between 0.19- and 1.50-fold for RCO2, depending on the temperatures). The cheese coated with the galactomannan coating was the one with the lower values of RO2 (between 0.195 and 0.635 mL kg−1 h−1) and RCO2 (between 0.125 and 0.900 mL kg−1 h−1). Temperature was also found to have an important effect on RO2 and RCO2, its influence being well described by an Arrhenius equation with coefficients of determination, R2, of 0.85 and above. The chemical and microbiological analyses showed that the application of the coating in cheese samples can be used to decrease the water loss and the colour changes during the storage time. The presence of the coating decreased the moisture loss of the cheese in 2.5% and 1.9%, and the weight loss in 3.8% and 3.1% at 4 °C and 20 °C, respectively. Also, the hardness of the cheese can be decreased as a result of the interaction of the presence of the coating with changes in the storing temperature. In the studied range (4–20 °C) temperature has a statistically significant effect in moisture loss, colour change, hardness and total mesophilic bacterial growth. Overall, galactomannan coating can be used to improve “Regional” cheese shelf-life as it decreases RO2 and RCO2, improves its weight and appearance and can be used to incorporate natural preservatives to reduce post contamination.